The Concept Of Educational Evaluation In Islamic Perspective - Umi Septina Anggraheni; Abid Nurhuda; Syukron Ni’am; Siti Jaroyatun Ni’mah (PT. Islamic Research Publisher, 2023)
Success or targets to be achieved in an activity must be measured by a tool called evaluation, especially in the field of education. As for Islam itself, the position of evaluation is very important where the Prophet exemplified it when he carried out the task of treatises and da'wah from Allah, the purpose of this study is to describe the concept of educational evaluation from an Islamic perspective. The method used is a qualitative literature study, data collection is documentation, then the contents are analyzed and concluded. The results of the study show that the Concept of Educational Evaluation from an Islamic Perspective must be carried out in a comprehensive manner which includes aspects of knowledge, attitudes, and skills where all of these things have also been exemplified by the Prophet when evaluating his companions.